2010
DOI: 10.3109/17453674.2010.519169
|View full text |Cite
|
Sign up to set email alerts
|

Effects of metal-on-metal wear on the host immune system and infection in hip arthroplasty

Abstract: Background and purposeJoint replacement with metal-on-metal (MOM) bearings have gained popularity in the last decades in young and active patients. However, the possible effects of MOM wear debris and its corrosion products are still the subject of debate. Alongside the potential disadvantages such as toxicity, the influences of metal particles and metal ions on infection risk are unclear.MethodsWe reviewed the available literature on the influence of degradation products of MOM bearings in total hip arthropla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
51
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(52 citation statements)
references
References 118 publications
1
51
0
Order By: Relevance
“…The whole issue of surgical site infection is complex, and if ever there was good use for the word multifactorial, it would be to describe the possible causes of PJI. Adverse cellular reaction with inflammation and necrosis in the THA pseudocapsule can provide a favorable environment for bacterial proliferation, a potential reason as to why the incidence of PJI may be higher in THA with MoM bearings [6]. In contrast, the synovial-like pseudocapsule found in CoC THAs with fibrous tissue and limited inflammatory changes may potentially reduce the bioburden for late deep infection.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…The whole issue of surgical site infection is complex, and if ever there was good use for the word multifactorial, it would be to describe the possible causes of PJI. Adverse cellular reaction with inflammation and necrosis in the THA pseudocapsule can provide a favorable environment for bacterial proliferation, a potential reason as to why the incidence of PJI may be higher in THA with MoM bearings [6]. In contrast, the synovial-like pseudocapsule found in CoC THAs with fibrous tissue and limited inflammatory changes may potentially reduce the bioburden for late deep infection.…”
Section: Discussionmentioning
confidence: 88%
“…The 2015 New Zealand Joint Registry report identified PJI as the fifth most common reason for primary THA revision, accounting for 12% of THA revisions (452 of 3914 revisions); only dislocation, aseptic loosening of the acetabular component, aseptic loosening of the femoral component, and pain were more common [16]. Recently, the type of bearing surface and the potential association with infection have been the subject of investigation [6]. Limited observational data show a higher association of infection with metal-on-metal bearings than with other kinds [2].…”
Section: Introductionmentioning
confidence: 99%
“…This results in progressive local osteolysis that threatens the fixation of the hardware (2). Whilst polyethylene degrades through wear alone, the metal alloys used in orthopaedic implants also degrade due to corrosion, or a combination of wear and corrosion (3,4).…”
Section: Orthopaedic Biomaterials Degradationmentioning
confidence: 99%
“…However, particles are still produced as a result of wear and corrosion and this may cause osteolysis and eventually failure of the prosthesis (Billi et al, 2009;Hosman et al, 2010;Catelas et al, 2003). Following implantation, the responses that occur at the interface of a biomaterial and in the surrounding environment are important events in determining the biocompatibility of the implant.…”
Section: Discussionmentioning
confidence: 99%
“…This passive film prevents degradation of the alloys as is one of the kinetic barriers preventing implant corrosion (Arnholt et al, 2016). However, due to wear, electrochemical dissolution, or a combination of the 2 processes, micro and nanometric sizes wear particles are still produced and metallic ions are released from the prosthesis of the implanted patients (Billi et al, 2009;Hosman et al, 2010;Arnholt et al, 2016). Catelas et al (2003) have reported the necessity to carry out in vitro studies of the effects of these wear particles rather than the effect of CoCrMo particles on tissue response.…”
Section: Introductionmentioning
confidence: 99%